Intricate diagnosis due to falsely elevated testosterone levels by immunoassay - Gardini, Benedetta; Bondanelli, Marta; Cariani, Alessio; Zatelli, Maria Chiara; Ambrosio, Maria Rosaria (Endocrine, 2025)
Purpose Hormone immunoassay may be subject to interferences and, although rarely reported, this can occur for testosterone too. This work is aimed to highlight the importance of considering possible analytical interferences when the biochemical data doesn’t match with the clinical picture. Methods We report three cases of insidious diagnosis due to laboratory interference in testosterone immunoassay, and we provide a brief literature review on this issue. Results We found falsely high testosterone levels due to the presence of heterophilic antibodies, leading to unnecessary investigations, misdiagnosis and inappropriate treatments. Conclusion The detection of elevated testosterone levels on immunoassay not corresponding to clinical findings need to be confirmed by liquid chromatography-tandem mass spectroscopy, prior to escalation of complex diagnostic investigation and care.